1987
DOI: 10.1148/radiology.163.1.3454163
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-labeled liposomes: targeted MR contrast agents for the liver and spleen.

Abstract: A contrast agent for use in magnetic resonance (MR) imaging of the liver and spleen has been designed in which gadolinium-DTPA is chemically incorporated into the lamellar phase of liposome particles. This agent has excellent in vivo stability and is taken up by liver and spleen of normal mice after intravenous administration. The T1 increased by 110% in liver and 66% in spleen at 4 degrees C. At 37 degrees, the relaxation rate in the liver increased by 180%. This method is an attractive concept for the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…Ordinarily, because every spin's precession frequency is proportional to the local magnetic field, the frequency spectrum I(ω) faithfully mirrors the spin density Diffusion is generally expected to contribute to blurring of images. For example, studies on paramagnetic contrast agents have shown that biological contours are blurred since contrast agents affect not only the tissue compartments to which they are confined but, through diffusive water exchange, also affect surrounding regions (7,8,9,10,11). Thus, one might expect that diffusion blurring should become prevalent in microscopic imaging, yet this may not necessarily be the case.…”
Section: Theorymentioning
confidence: 99%
“…Ordinarily, because every spin's precession frequency is proportional to the local magnetic field, the frequency spectrum I(ω) faithfully mirrors the spin density Diffusion is generally expected to contribute to blurring of images. For example, studies on paramagnetic contrast agents have shown that biological contours are blurred since contrast agents affect not only the tissue compartments to which they are confined but, through diffusive water exchange, also affect surrounding regions (7,8,9,10,11). Thus, one might expect that diffusion blurring should become prevalent in microscopic imaging, yet this may not necessarily be the case.…”
Section: Theorymentioning
confidence: 99%
“…This myocardial specificity of Gd(BME-DTTA) was also observed in our studies in ferret and dog ischemia models using liposomal Gd(BME-DTTA). 2,12,13 The average particle size of liposomal Gd(BME-DTTA), observed in the electron micrographs, is smaller than 0.125 m. It has been reported that small liposome particles (average 0.1 m) are more effectively taken up by hepatocytes 14,15 and the spleen 16 than larger ones. Therefore, the large IE effects observed in liver and spleen may be attributed to the relatively small size of the liposomal Gd(BME-DTTA) particles.…”
Section: Discussionmentioning
confidence: 99%
“…After administration of 50 anoi Fe/kg of fernte, the signal-to-ncise ratio of spleen was significantly (p < .005) less than that of tumor. [22], and liposomes containing paramagnetic ions such as gadolinium [23] or manganese [24]. For all of these drugs, either they are very toxic [20,21] or their toxicity has not been fully studied [ …”
Section: In Vivo Imagingmentioning
confidence: 99%